The Effect of Planning and Supervision in Improving Marketing Services Towards Prospective Students at The Aneka Pratama Edukasi Foundation - Endang Wahyuti; Zulkifli Rangkuti; Nurwulan Kusumadevi (Dinasti International Journal of Management Science, 2026)
The purpose of this study is as follows: To determine the effect of planning on improving marketing services to prospective students, To determine the effect of supervision on improving marketing services to prospective students and To determine the effect of planning and supervision simultaneously on improving marketing services. The results of the t test show that the calculated t value is greater than the t table and the significance level is less than 0.05, so the hypothesis stating that there is an influence of Planning on marketing services can be accepted, Supervision has a significant effect on marketing services to prospective students. Based on the results of the t test, the Supervision variable has a significant effect on marketing services. Effective supervision is able to ensure that the implementation of marketing activities runs according to plans, operational standards, and predetermined objectives, Planning and Supervision simultaneously have a positive and significant effect on marketing services to prospective students. The results of the F test show that the calculated F value is much greater than the F table with a significance level below 0.05. This shows that Planning and Supervision together have a very important role in improving the quality of marketing services.